Transmission of Vaccination Attitudes and Uptake Based on Social Contagion Theory: A Scoping Review - Konstantinou, Pinelopi; Georgiou, Katerina; Kumar, Navin; Kyprianidou, Maria; Nicolaides, Christos; Karekla, Maria; Kassianos, Angelos P. (My University, 2021)
Vaccine hesitancy is a complex health problem, with various factors involved including the influence of an individual's network. According to the Social Contagion Theory, attitudes and behaviours of an individual can be contagious to others in their social networks. This scoping review aims to collate evidence on how attitudes and vaccination uptake are spread within social networks. Databases of PubMed, PsycINFO, Embase, and Scopus were searched with the full text of 24 studies being screened. A narrative synthesis approach was used to collate the evidence and interpret findings. Eleven cross-sectional studies were included. Participants held more positive vaccination attitudes and greater likelihood to get vaccinated or vaccinate their child when they were frequently exposed to positive attitudes and frequently discussing vaccinations with family and friends. We also observed that vaccination uptake was decreased when family and friends were hesitant to take the vaccine. Homophily-the tendency of similar individuals to be connected in a social network-was identified as a significant factor that drives the results, especially with respect to race and ethnicity. This review highlights the key role that social networks play in shaping attitudes and vaccination uptake. Public health authorities should tailor interventions and involve family and friends to result in greater vaccination uptake.
Keywords: Vaccination; Immunization; Vaccine hesitancy; Social contagion theory; Social network analysis; Scoping review